On ?-statistical convergence and strongly ?-summable functions of order ? - Et, Mikail; Mohiuddine, Syed Abdul; Alotaibi, Abdullah (Springeropen, 2013)
In this study, using the notion of (V, lambda)-summability and lambda-statistical convergence, we introduce the concepts of strong (V, lambda, rho)-summability and lambda-statistical convergence of order alpha of real-valued functions which are measurable (in the Lebesgue sense) in the interval (1, infinity). Also some relations between.-statistical convergence of order alpha and strong (V, lambda, rho)-summability of order beta are given.
Keywords: statistical convergence; measurable function; (V, lambda)-summability